Effect of weather variables on the density of aedes mosquitoes in Johor Bahru Tengah : a retrospective study from 2014 - 2016 / Faridatul Akma Abdul Ghani - Abdul Ghani, Faridatul Akma (2018)
Dengue fever is one of the common diseases in Malaysia. Dengue fever is a communicable disease that known as vector borne disease. The vector of dengue fever is Aedes mosquitoes. The objective of this study to assess the effect of weather variables on the density of Aedes mosquitoes in Johor Bahru Tengah. This study using a retrospective cross study from 2014 to 2016. The data of Aedes indices and weather variables was collected by epid week for the three year. The Aedes indices data are represent by using cumulative percentage curve with the dengue fever cases. The Pearson’s correlation coefficient is calculated for each year by weekly cumulative percentage of Aedes index, breteau index and dengue cases. The weather pattern characteristics with Aedes indices are represent in the histogram and the line graph. While for each weather variables is present in the scatter plot graph. The relationship between Aedes indices and weather variables is measured using the Pearson’s correlation coefficient. The result showed no significant and low correlation between the Aedes indices and weather variables. Even the result showed low correlation, this study data collection can be used as the predicted outbreak of dengue fever. In addition, this study can identify the issue in the outbreak localities with the high Aedes index and breteau index.